Does High Caregiver Stress Predict Nursing Home Entry? - Brenda C. Spillman; Sharon K. Long (SAGE Publishing, 2009)
This study estimates how informal care, paid formal care, and caregiver stress or burden relate to nursing home placement. Data came from the 1999 National Long Term Care Survey and were merged with administrative data. Results show that stress is a strong predictor of entry over follow-up periods of up to two years, and physical strain and financial hardship are important predictors of high levels of caregiver stress. The estimates indicate that reducing these stress factors would significantly reduce caregiver stress and, as a result, nursing home entry. We conclude that initiatives to reduce caregiver stress hold promise as a strategy to avoid or defer nursing home entry.